Differential expression of PSMC4, SKP1, and HSPA8 in Parkinson’s disease: insights from a Mexican mestizo population - Salas-Leal, Alma C.; Salas-Pacheco, Sergio M.; Hernández-Cosaín, Erik I.; Vélez-Vélez, Lilia M.; Antuna-Salcido, Elizabeth I.; Castellanos-Juárez, Francisco X.; Méndez-Hernández, Edna M.; Llave-León, Osmel La; Quiñones-Canales, Gerardo; Arias-Carrión, Oscar; Sandoval-Carrillo, Ada A.; Salas-Pacheco, José M. (Frontiers in Molecular Neuroscience, 2023)
Parkinson's disease (PD) is a complex neurodegenerative condition characterized by alpha-synuclein aggregation and dysfunctional protein degradation pathways. This study investigates the differential gene expression of pivotal components (UBE2K, PSMC4, SKP1, and HSPA8) within these pathways in a Mexican-Mestizo PD population compared to healthy controls. We enrolled 87 PD patients and 87 controls, assessing their gene expression levels via RT-qPCR. Our results reveal a significant downregulation of PSMC4, SKP1, and HSPA8 in the PD group (p=0.033, p=0.003, and p=0.002, respectively). Logistic regression analyses establish a strong association between PD and reduced expression of PSMC4, SKP1, and HSPA8 (OR=0.640, 95% CI=0.415-0.987; OR=0.000, 95% CI=0.000-0.075; OR=0.550, 95% CI=0.368-0.823, respectively). Conversely, UBE2K exhibited no significant association or expression difference between the groups. Furthermore, we develop a gene expression model based on HSPA8, PSMC4, and SKP1, demonstrating robust discrimination between healthy controls and PD patients. Notably, the model's diagnostic efficacy is particularly pronounced in early-stage PD. In conclusion, our study provides compelling evidence linking decreased gene expression of PSMC4, SKP1, and HSPA8 to PD in the Mexican-Mestizo population. Additionally, our gene expression model exhibits promise as a diagnostic tool, particularly for early-stage PD diagnosis.